Thrombin generation predicts early recurrence in breast cancer patients. (11th August 2020) - Marchetti, Marina; Giaccherini, Cinzia; Masci, Giovanna; Verzeroli, Cristina; Russo, Laura; Celio, Luigi; Sarmiento, Roberta; Gamba, Sara; Tartari, Carmen J.; Diani, Erika; Vignoli, Alfonso; Malighetti, Paolo; et al.
Abstract: Background: Cancer patients present with a hypercoagulable state often associated with poor disease prognosis. Objectives: This study aims to evaluate whether thrombin generation (TG), a global coagulation test, may be a useful tool to improve the identification of patients at high risk of early disease recurrence (ie, E‐DR within 2 years) after breast cancer surgery. Patients/Methods: A cohort of 522 newly diagnosed patients with surgically resected high‐risk breast cancer were enrolled in the ongoing prospective HYPERCAN study. TG potential was measured in plasma samples collected before starting systemic chemotherapy. Significant predictive hemostatic and clinic‐pathological parameters were identified in the derivation cohort by Cox regression analysis. A risk prognostic score for E‐DR was generated in the derivation and tested in the validation cohort. Results: After a median observation period of 3.4 years, DR occurred in 51 patients, 28 of whom were E‐DR. E‐DR subjects presented with the highest TG values as compared to both late‐DR (from 2 to 5 years) and no relapse subjects ( P < .01). Multivariate analysis in the derivation cohort identified TG, mastectomy, triple negative and Luminal B HER2‐neg molecular subtypes as significant independent predictors for E‐DR, which were utilized to generate a risk assessment score. In the derivation and validation cohorts, E‐DR rates were 2.3% and 0% in the low‐risk, 10.1% and 6.3% in the intermediate‐risk, and 18.2% and 16.7%, in the high‐risk categories, respectively. Conclusions: Inclusion of TG in a risk‐assessment model for E‐DR significantly helps the identification of operated breast cancer patients at high risk of very early relapse.